(untitled) (Innovate Conferences, 2025)
The deepening of market relations, the growing complexity of economic ties and the expansion of property turnover require the stable and consistent development of the institution of contract law. One of the most important aspects of the system of contract law is the criteria for determining the validity of contracts and the procedure for declaring them invalid. This institution is of fundamental importance in both legal systems – Islamic law and the civil legislation of Uzbekistan – as it serves to ensure stability in civil turnover, protect the interests of the parties and guarantee adherence to the principles of justice.